The viticulture labor in Mendoza (Argentina) during the capitalist modernization, 1880-1914 - Richard-Jorba, Rodolfo (Centro de Historia Argentina y Americana, 2009)
This paper outlines the development process of the capitalist viticulture in Mendoza. Using different primary and secondary sources, this study determines the composition of the viticulture labor and its quantitative and qualitative evolution. The introduction of up to date technology forced the training of manual labor with visible improvements in the workers' pay checks. This market became more complex through time showing multiple hierarchies in every rank of the work force, from peasants to wine makers. Several workers ascended the social ladder becoming managers due to diverse strategies traced through our various sources. Finally the workers' labor conditions indicate the vulnerability in which they were involved and their helplessness due to the lack of unions that could represent them